A note on Ostrowski and Gr"uss type discrete inequalities - Pachpatte, B. G. (Tamkang Journal of Mathematics, 2004)
The aim of the present note is to establish some new discrete inequalities of the Ostrowski and Gr"uss type involving two functions and their forward differences.